Influence of exercise test on platelet function in patients with coronary arterial disease: A systematic review. Issue 8 (26th February 2021) - Mo, Chunhua; Wang, Yanhui; Yue, Zong; Hu, Dayi; Yin, Chun
Abstract: Background: Exercise test (ET) may have adverse effects on platelet function and induce acute thrombotic events in patients with coronary artery disease (CAD). The aim of this study is to investigate the platelet function and evaluate the risk of thrombotic events in CAD patients during ET. Methods: Pubmed, Embase, Cochrane Library, and Web of Science were searched for a systematic review from initiation to October 2019. The inclusion criteria were controlled clinical trails as study design; investigating platelet function in CAD patients during ET; with ET carried out by treadmill or bicycle ergometer; written in English. Included articles were screened based on title/abstract and full-text review by 2 independent reviewers. Platelet aggregation (PA), platelet surface expression of CD62p and PAC-1, plasma levels of platelet factor 4 (PF4) and beta-thromboglobulin ( β -TG) were evaluated before and after ET. Results: Eighteen articles were included out of the 427 references initially identified. In most of the studies included ET was terminated because of limited symptoms. Prior to ET, no difference in platelet aggregation was observed in CAD patients compared with healthy controls in majority of the studies, with or without the treatment with Aspirin. Dual anti-platelet therapy suppressed adenosine diphosphate (ADP)-induced platelet aggregation at rest. After ET, platelet aggregation, the serum levels of β-thromboglobulin were found unchanged in majority of studies and platelet factor-4 were found unchanged in half of studies. The expression of platelet surface markers were elevated by ET in a few study. Conclusion: Symptom-limited exercise test did not affect platelet function in patients with coronary artery disease; however exercise to higher intensity may induce platelet activation.